Women's Participation in Tourist Village Empowerment - Yuliana Kusumadewi, Eti Solikhatun; Sari, Lilik Kartika; Sulaiman, Adhi Iman; Wuryaningsih, Tri; Prastyanti, Shinta (Tecno Scientifica Publishing, 2023)
Community participation is an important part of the implementation of community empowerment, which is generally carried out in the village. Women's participation, as a form of reducing gender inequality, contributes to efforts to maintain and develop tourism villages. The research aims to analyze the practice of women's participation in Cikakak Tourism Village. The research method used is a mixed method with data collection techniques including distributing questionnaires, conducting Focus Group Discussions, conducting in-depth interviews, and observation. The research informants include women's participation actors, such as family welfare empowerment groups, women farmers groups, business groups, and the village head. The research employs a qualitative research approach with a case study methodology. The results of the study show that women's participation in Cikakak Tourism Village has been carried out voluntarily and democratically, involving them in the process of planning and decision-making for Tourism Village activities, with a tendency towards a representative system. The women have contributed in various forms, such as in-kind contributions, labor, expertise or skills, and monetary contributions, which are adjusted based on the individual's capabilities. The most common form of contribution made by women is in the form of labor.